KEDISIPLINAN KARYAWAN DAN PENGARUHNYA TERHADAP KUALITAS KERJA PADA MANADO QUALITY HOTEL - Walansendow, Agustinus; Mananeke, Lisbeth; Pasambe, Yorisal (Jurnal Hospitaliti, 2023)
The aim of this research is to analyze, measure and explain employee discipline and its influence on work quality at the Manado Quality Hotel. In this research, the techniques used were observation, surveys and interviews. The sampling method was taken at random or random sampling and the analysis method used was simple linear regression analysis where the variable (X) Employee Discipline and the variable (Y) Work Quality with the equation Y'=a+bX and correlation coefficient analysis to calculate how strong the relationship is. between variable (X) and variable (Y).The final results of this research after carrying out simple linear regression analysis calculations obtained an equation where Y' = 3.46 + 0.98 and vice versa. Determinant coefficient r2 = 0.4624 or 46.24%. This shows that there is a strong influence on work quality, 46.24% and 53.76% are changes in variables caused by factors that are not researched, such as management policies and employee work system settings.